PERANAN PENDIDIKAN ORANG TUA DALAM MEMOTIVASI BELAJAR SISWA SMA MUHAMMADIYAH 4 BANDUNG - Riyandi (UNISAN JURNAL, 2023)
The purpose of this study was to find out how parental education influences student learning motivation and what factors influence the role of parents in motivating student learning. The research method used is descriptive qualitative with data collection techniques through interviews and observations of 10 students of SMA Muhammadiyah 4 Bandung City and their parents. The results of the study show that parental education is very important in motivating learning for SMA Muhammadiyah 4 Bandung City students. Parents who provide proper support, encouragement, and supervision can increase student learning motivation. Factors that influence the role of parents in motivating student learning include parents' educational level, communication between parents and children, financial support, and parenting styles. This research recommends that parents can increase their role in motivating children's learning by providing the right support and encouragement, as well as improving communication between parents and children. In addition, schools can provide socialization to parents regarding the importance of their role in children's education.